1998
DOI: 10.1007/s004250050471
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of a new vegetative MADS-box gene from Solanum tuberosum L.

Abstract: A cDNA clone, STMADS11, encoding a new MADS-box protein was isolated from Solanum tuberosum L. (potato). Expression of STMADS11 was found in all vegetative organs of the plant, but not in floral tissues. The expression was also detected in all developmental stages, from tuber sprouts to mature plants, reaching a maximum in well-developed organs. However, the level of STMADS11 mRNA was low in tissues such as resting tuber or sprouts developed in the cold, where the metabolic activity is reduced. "In situ" hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…1). Sequence comparison with several MADS-box proteins from monocots and dicots revealed that TaVRT-2 is homologous to MADS-box proteins from the StMADS11-like clade (Carmona et al, 1998;Becker and Theissen, 2003). TaVRT-2 shows 96% amino acid sequence identity with its reconstructed ortholog from barley (Hordeum vulgare; named HvVRT-2), 77% with two proteins from maize (Zea mays; ZmM19 and ZmM26), 73% with a protein from rice (OsMADS22), and 51% with the SHORT VEGETATIVE PHASE protein from Arabidopsis (AtSVP), the closest predicted homolog from dicot species (Supplemental Table II).…”
Section: Identification and Molecular Characterization Of Tavrt-2mentioning
confidence: 99%
See 2 more Smart Citations
“…1). Sequence comparison with several MADS-box proteins from monocots and dicots revealed that TaVRT-2 is homologous to MADS-box proteins from the StMADS11-like clade (Carmona et al, 1998;Becker and Theissen, 2003). TaVRT-2 shows 96% amino acid sequence identity with its reconstructed ortholog from barley (Hordeum vulgare; named HvVRT-2), 77% with two proteins from maize (Zea mays; ZmM19 and ZmM26), 73% with a protein from rice (OsMADS22), and 51% with the SHORT VEGETATIVE PHASE protein from Arabidopsis (AtSVP), the closest predicted homolog from dicot species (Supplemental Table II).…”
Section: Identification and Molecular Characterization Of Tavrt-2mentioning
confidence: 99%
“…2). Transcription factors of this clade have been associated with the repression of transition of the shoot apex from the vegetative to the reproductive phase (Carmona et al, 1998;Becker and Theissen, 2003).…”
Section: Identification and Molecular Characterization Of Tavrt-2mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, AGL20/SOC1 is regulated by both AGL22/SVP and AGL24 (refs 18, 19), which are floral meristem identity genes with redundant functions during early stages of flower development 21 . The StMADS11 gene does not appear to have a direct orthologue in A. thaliana, but in potato (S. tuberosum) StMADS11 is expressed in vegetative tissues 106 . Despite their well-known roles in floral regulation, SVP/StMADS11 and SOC1/TM3 proteins are likely to have wider functions.…”
mentioning
confidence: 99%
“…One subgroup, formed by the MIKC c -type genes, is best known for its important role in the control of flower development (reviewed in 12). Some MIKC c -type MADSbox genes, however, have functions outside of flower development and are mainly expressed in vegetative organs, for example, the STMADS11-like genes (13)(14)(15). MADS-box gene functions are frequently conserved between plant species and confer comparable organ identities in different species (16).…”
mentioning
confidence: 99%